Challenges of Using High-Dose Fractionation Radiotherapy in Combination Therapy - Yang, Ying-Chieh; Chiang, Chi-Shiun (Frontiers in Oncology, 2016)
Radiotherapy (RT) is crucial and substantially contributes to multimodal cancer treatment. The combination of conventional fractionation radiotherapy (CFRT) and systemic therapy has been established as the standard treatment for many cancer types. With advances in linear accelerators and image-guided techniques, high-dose fractionation radiotherapy (HFRT) is increasingly introduced in cancer centers. Clinicians are currently integrating HFRT into multimodality treatment. The shift from CFRT to HFRT reveals different effects on the tumor microenvironment and responses, particularly the immune response. Furthermore, the combination of HFRT and drugs yields different results in different types of tumors or using different treatment schemes. We have reviewed clinical trials and preclinical evidence on the combination of HFRT with drugs such as chemotherapy, targeted therapy, and immune therapy. Notably, HFRT apparently enhances tumor cell killing and antigen presentation, thus providing opportunities and challenges in treating cancer.